If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7906(99x + -89) = 0 Reorder the terms: -7906(-89 + 99x) = 0 (-89 * -7906 + 99x * -7906) = 0 (703634 + -782694x) = 0 Solving 703634 + -782694x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-703634' to each side of the equation. 703634 + -703634 + -782694x = 0 + -703634 Combine like terms: 703634 + -703634 = 0 0 + -782694x = 0 + -703634 -782694x = 0 + -703634 Combine like terms: 0 + -703634 = -703634 -782694x = -703634 Divide each side by '-782694'. x = 0.898989899 Simplifying x = 0.898989899
| f(2)=2(2)+3 | | 5[3x-4]=8[x+2]+5 | | 45.2-5h=2.8 | | -2(5-8)+6*5= | | 20=-6(-9-3x) | | 3x-2(5-x)=5(x-2) | | (x-1)(2x+6)=104 | | 7(-8m+2)=-434 | | 4=-(x-7)+3 | | 21dy+6xy-6xv-21dv= | | 8x+(-5)=35 | | Y=1.03x | | 2y+3y+30+4x-100+x+5=360 | | f(1)=1(1)+3 | | vw+uw=uv | | 2x+(x+6)=54 | | -2a-6a=24 | | (w^2-4w+7)+(3w^2+5w-3)= | | 2y-36x=45-38y | | 1350=45x+30y | | 10=8-4y | | 3x*ln(x+3)+4=0 | | 11w+2(3w-1)=5 | | (9y-6)(1.5)+3.5y= | | 3.50x+40=57.50 | | 7n+n=64 | | 30x^2-25x=0 | | 2(2x+3)=24 | | -2c-24=2c-12 | | 9u-5u=36 | | 5x+2=-5 | | 6-3x=14x+2 |